The social representation of the Trans collective in current advertising: the Pantene case - Valecillos Vázquez, Carmen; Martínez Escudero, Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this research is to determine the social representation that, of the trans collective, builds the advertising of Pantene in the ad: "Recreated family photo". The campaign is novel because it aims to combat stereotypes imposed by society in relation to physical appearance and because it works with a minority of the LGTBIQ+ community, prone to being victims of hate crimes. The content analysis carried outallows us to conclude that although the message aims to positively influence both trans people and society, an incomplete social representation of the collective is still offered.